2022
DOI: 10.1007/s12525-022-00592-6
|View full text |Cite
|
Sign up to set email alerts
|

User trust in artificial intelligence: A comprehensive conceptual framework

Abstract: This paper provides a systematic literature review of current studies between January 2015 and January 2022 on user trust in artificial intelligence (AI) that has been conducted from different perspectives. Such a review and analysis leads to the identification of the various components, influencing factors, and outcomes of users' trust in AI. Based on the findings, a comprehensive conceptual framework is proposed for a better understanding of users' trust in AI. This framework can further be tested and valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 161 publications
1
26
0
Order By: Relevance
“…Similarly, Jing et al (2020) conducted a literature review and discovered a negative correlation between perceived uncertainties and risks with the acceptance of autonomous driving. Furthermore, perceived uncertainties in the application of AI vary across different applications, particularly pronounced in medical expert systems and vehicles ( Yang and Wibowo, 2022 ).…”
Section: A Three-dimension Framework Of Trust In Aimentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Jing et al (2020) conducted a literature review and discovered a negative correlation between perceived uncertainties and risks with the acceptance of autonomous driving. Furthermore, perceived uncertainties in the application of AI vary across different applications, particularly pronounced in medical expert systems and vehicles ( Yang and Wibowo, 2022 ).…”
Section: A Three-dimension Framework Of Trust In Aimentioning
confidence: 99%
“…The invention of generative AI technologies, such as ChatGPT, marks a particularly significant leap in AI’s competence. While bringing significant changes to society, the development of AI has also sparked various concerns, including privacy invasion, hidden biases and discrimination, security risks, and ethical issues ( Yang and Wibowo, 2022 ). One response to these concerns is the emergence of and emphasis on trustworthy AI that aims to strike a good balance between technological advancement and societal and ethical considerations ( Li et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that attitudes toward AI can significantly influence brand trust (Qin et al, 2020 ; Ahn et al, 2022 ; Yang and Wibowo, 2022 ). For instance, in the realm of e-commerce, studies have underscored the role of trust in online vendors and merchants in mitigating the perceived risks of online transactions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors' framework is specific to AI. The Foundational Trust Framework can be used in conjunction with this paper to better understand the nature of trust in AI (Yang & Wibowo, 2022). • The paper "The effect of transparency and trust on intelligent system acceptance: evidence from a user-based study" by Jonas Wanner, Lukas-Valentin Herm, Kai Heinrich, and Christian Janiesch reports on a study related to trust in AI.…”
Section: Special Issue On "Trust In Ai" In Electronic Marketsmentioning
confidence: 99%